ĐÁNH GIÁ ĐẶC ĐIỂM Ô NHIỄM ASEN TRONG NƯỚC VÀ TRẦM TÍCH SÔNG ĐÁY BẰNG CÁC PHƯƠNG PHÁP THỐNG KÊ VÀ HỆ THỐNG THÔNG TIN ĐỊA LÝ (GIS) - Nguyễn, Kim Thuỳ; Lê, Bảo Hưng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF ARSENIC POLLUTION CHARACTERISTICS IN WATER AND SEDIMENT OF THE DAY RIVER BASIN SYSTEM USING STATISTICAL METHODS AND GEOGRAPHICAL INFORMATION SYSTEM (GIS)In the article As contents of water, sediment and suspended solids of the Day River Basin are identified and treated using statistical methods and GIS. It was found that the concentration of As in water samples is lower than permitted standards, but in sediment samples it is much higher than the permitted standards, which could be caused by high concentration of iron oxide of the sediments. The application of statistical analysis and GIS shows that the concentrations of As in water and sediment samples are not influenced by river flow, but by geological factors and human activities. The finding also shows the ability to combine statistical methods and GIS in studying environmental pollution.